Cryogenic Mixed Refrigerant Processes - Gadhiraju, Venkatarathnam; Timmerhaus, Klaus D.; Rizzuto, Carlo; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
Cryogenic refrigerators operating with refrigerant mixtures were developed under classified and proprietary programs for many years, and it was only after 1991 that the world realized the importance of the mixed refrigerant systems for cryogenic refrigeration. Mixed refrigerant cryogenic processes are also used in most large base load natural gas liquefaction plants. Hundreds of patents exist on different aspects of mixed refrigerant processes for liquefaction of natural gas, as well as the composition of mixtures for Joule-Thomson and other refrigerators. Still, the fundamental aspects of these processes continued to not receive the attention they deserve in open literature in the view of these commercial interests. Cryogenic Mixed Refrigerant Processes, by Dr. G. Venkatarathnam, explains all the aspects of mixed refrigerant processes using robust analytical methods based on sound thermodynamic principles, drawing upon many case studies and examples, largely unpublished, to teach: - the need for refrigerant mixtures - the different processes than can be used in refrigeration and liquefaction systems - the methods to be adopted for choosing the components of a mixture and their concentrations used for various cryogenic applications - the methods for simulating and optimizing cryogenic processes Cryogenic Mixed Refrigerant Processes will be a valuable and much needed reference for researchers and scientists whose focus includes cryogenic engineering, natural gas liquefaction, refrigeration systems, and process simulation and optimization. Dr. G. Venkatarathnam is Professor of Mechanical Engineering at the Indian Institute of Technology Madras, India. (3z$1! =(Bthis is a good reference both for entering the domain of mixed refrigerant processes, and to expand the knowledge of optimal applications for this technique. It is a compact book that gives practical answers on the why and how to use mixtures in cryogenics.(3y (B-Luca Bottura, CERN, Switzerland (3z(BThis book is an important source of knowledge for post-graduate students, process engineers working on equipment projects for gas liquefaction industry as well as those, operating liquefaction plants, or for feasibility studies analysts, as well as for newcomers in this branch of technology. Reading of the book doesn$1 (Bt require any previous specific knowledge except of basic course of thermodynamics on university level. All readers will certainly appreciate the work done by the author on optimization of all the cycles. It may save a lot of research and engineering work of those working on projects. Possibly, it can also help to achieve more optimized solutions.(3y (B-Vaclav Chrz, Chart Ferox, Czech Republic.s
Fundamental principles and processes -- Simulation of cryogenic processes -- Need for refrigerant mixtures -- Constant-temperature refrigeration processes -- Optimum mixture composition -- Natural gas liquefaction processes -- Cooling and liquefaction of air and its constituents.
Keywords: Chemistry; Chemical engineering; Solid state physics; Superconductivity; Superconductors; Spectroscopy; Microscopy; Materials science; Chemistry; Industrial Chemistry/Chemical Engineering; Strongly Correlated Systems, Superconductivity; Solid State Physics; Spectroscopy and Microscopy; Materials Science, general; Electronic books